Some other note the lost songs of English Renaissance comedy - Duffin, Ross W. 1951- (Oxford University Press, 2018)
English comedy from the fifteenth to the early seventeenth century abounds in song lyrics, but most of the original tunes were thought to have been lost—until now. By deducing that playwrights borrowed melodies from songs they already knew, Ross W. Duffin has used the existing English repertory of songs, both popular and composed, to reconstruct hundreds of songs from more than a hundred plays and other stage entertainments. Thanks to Duffin's incredible breakthrough, these plays have been rendered performable with period music for the first time in five hundred years. Some Other Note not only brings these songs back from the dead, but tells a thrilling tale of the investigations that unraveled these centuries-old mysteries. - A native of Canada, Ross W. Duffin is Fynette H. Kulas Professor of Music and Distinguished University Professor at Case Western Reserve University, where he specializes in historical performance practice. Among his books are Shakespeare's Songbook (W. W. Norton, 2004), and How Equal Temperament Ruined Harmony (and Why You Should Care) (Norton, 2007). Duffin has been described as "virtually synonymous with music and Shakespeare," and his book was lauded as "a musicological tour de force, totally without pedantry, a book which will forever change Shakespeare productions." (Klappentext)